PENINGKATAN LITERASI KEUANGAN DIGITAL MELALUI PEMANFAATAN PEMBAYARAN DIGITAL PADA PELAKU UMKM - Shafaratin Nurul Hasanah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2026)
The development of digital payment system technologies has driven significant changes in transaction behavior within society, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. One innovation initiated by Bank Indonesia is the Quick Response Code Indonesian Standard (QRIS), which serves as a national standard for QR code–based payments. However, the level of digital financial literacy and QRIS adoption among MSMEs, particularly in Pamekasan Regency, still faces several challenges, such as limited understanding of digital financial systems, low trust in non-cash payment methods, and a lack of technical assistance. This community service activity aims to improve digital financial literacy and enhance the capacity of MSME actors to utilize QRIS as a safe, efficient, and transparent payment instrument. The methods employed include socialization, training, direct mentoring, and evaluation of QRIS implementation among the targeted MSMEs. The results indicate an increase in MSME actors’ understanding of the benefits of QRIS, improved digital financial literacy, successful implementation of QRIS in business transactions, and better financial record-keeping practices. This activity is expected to contribute to increased financial inclusion and enhanced competitiveness of MSMEs in Pamekasan Regency